Exploring the role of classical elements in contemporary graphic design - JEFF POON CHAK KIN (International Journal of Multidisciplinary Research and Studies, 2023)
As the standard of living in China has risen thanks to the country's robust economic growth, more and more citizens are devoting time and energy to enriching their minds and souls. As a consequence of this context, traditional Chinese graphic motifs have been successfully integrated into contemporary graphic design. It has helped spread the word about graphic design, which has led to a more varied and expansive field. This article explores the real-world applications of traditional Chinese graphic elements in the context of contemporary graphic design; the aim is to provide some pointers and guidelines for the further evolution of the design's central components.